Bidentate-coordinated Mn/C catalyst for high-efficiency aerobic oxidation of cyclohexanone to adipic acid - Tun Wu; Haoyu Peng; Xilong Tu; Yani Liu; Liqiu Mao; Wenzhou Zhong (Applied Catalysis O: Open)
Adipic acid (AA), a crucial industrial dicarboxylic acid, faces sustainability challenges due to its conventional nitric acid-based production process that emits significant amounts of N2O greenhouse gas. This study introduces a novel carbon-supported catalyst for oxidative cleavage of cyclohexanone under O2 atmosphere, achieving 92.4 % AA selectivity. The catalyst, synthesized via a solution-based precursor followed by high-temperature carbonization, immobilizes manganese in a bidentate coordination on the carbon support. It exhibits remarkable stability over 10 cycles without metal leaching or performance decay. The effects of different carbon sources and transition metals on the catalyst were systematically investigated within this methodology, and comprehensive characterization using FT-IR, Py-IR, Raman spectra, ICP, XRD, XPS, SEM, TEM and BET was conducted. Analysis of the reaction process enabled proposal of a plausible mechanism. This work establishes a green AA synthesis route while advancing carbon-supported catalyst design through simplified, cost-effective strategies with enhanced stability.